Novel Drug Delivery Systems for Treating Ocular Surface Disorders - Jehan Zeb Khan, Syed Amir Hamza, Maria Sultan, Muhammad Waseem, Tahir Ali, Muhammad Zeeshan Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: OSDs represent a wide spread medical condition which produces uncomfortable vision and diminishes both visual function and patient satisfaction with their lives. The research analyzes how well NDDS performs relative to standard eye drop treatments for OSD treatment and examines patient medication use and safety results. Methodology: A six months research took place at the department of Ophthalmology, Mardan Medical Complex, Mardan and Bacha Khan Medical Complex, Swabi, through a prospective study which analyzed two groups against conventional eye drop therapy. Three treatment groups with separate assignments were established: the conventional eye drops group totaling 50 patients and the liposome-based group with 50 patients and a separate group allocated 50 patients for nanoparticle-based formulations. Researchers measured tear film breakup time (TFBUT) together with corneal staining scores and Ocular Surface Disease Index (OSDI) scores across three assessment periods beginning from baseline until week 4 and week 12. The researchers used ANOVA combined with paired t-tests for statistical evaluation (p<0.05). Results: The utilization of NDDS at 12 weeks provided TFBUT improvements with 12.6 ± 2.1 sec for liposomal and 13.1 ± 2.3 sec for nanoparticle compared to 8.4 ± 1.9 sec for conventional drops (p<0.001) and decreased corneal staining manifestations (p<0.001) and OSDI scores were more favorable (p<0.001). Patients adhered to treatment more frequently with NDDS compared to conventional drops since their usage rates reached 89% and 91% respectively (conventional drops had 65% adherence). Participants experienced no troubling adverse responses during the study duration. Conclusion: The Natural Decoctions Delivery Systems improved OSD management through their actions on tear film stability and reduced corneal damage and better adhesion. The alternative treatment systems appear promising for drop replacement however additional investigation must determine their long-term safety performance and economic impact. Keywords: Ocular surface disorders, drug delivery, liposomes, nanoparticles, tear film stability, corneal staining.